2016
DOI: 10.1002/1873-3468.12315
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA MALAT1 regulates the lipopolysaccharide‐induced inflammatory response through its interaction with NF‐κB

Abstract: MALAT1 is a conserved long noncoding RNA whose expression correlates with many human cancers. However, its significance in immunity remains largely unknown. Here, we observe that MALAT1 is upregulated in lipopolysaccharide (LPS)-activated macrophages. Knockdown of MALAT1 increases LPS-induced expression of TNFa and IL-6. Mechanistically, MALAT1 was found to interact with NF-jB in the nucleus, thus inhibiting its DNA binding activity and consequently decreasing the production of inflammatory cytokines. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
174
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(194 citation statements)
references
References 41 publications
10
174
1
1
Order By: Relevance
“…15 In consistent with the previous study, we also found that MALAT1 was upregulated in LPS-stimulated ATDC5 cells. 15 In consistent with the previous study, we also found that MALAT1 was upregulated in LPS-stimulated ATDC5 cells.…”
Section: 4 | Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…15 In consistent with the previous study, we also found that MALAT1 was upregulated in LPS-stimulated ATDC5 cells. 15 In consistent with the previous study, we also found that MALAT1 was upregulated in LPS-stimulated ATDC5 cells.…”
Section: 4 | Discussionsupporting
confidence: 93%
“…Puthanveetil et al 13 suggested that MALAT1 participated in the hyperglycemia-induced endothelial cell inflammatory injury. The experimental study from Zhao et al 15 proved that MALAT1 modulated the lipopolysaccharide (LPS)-stimulated inflammatory response by interacting NF-κB pathway. The experimental study from Zhao et al 15 proved that MALAT1 modulated the lipopolysaccharide (LPS)-stimulated inflammatory response by interacting NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…An independent group of researchers revealed that this miRNA additionally interferes in vitro with Th1 cell differentiation of human CD4 + T lymphocytes via PRKC [154]. Other miRNAs, including miR-124, miR-142-3p, and miR-195, have also been demonstrated to be useful in preventing hyperinflammation, apoptosis, and multiple organ injury in murine sepsis models [8, 140, 155, 156]. Similarly, indirect induction of miR-126 expression in vitro by CTEC-0214, a stromal cell-derived factor 1 alpha analog, preserved endothelial cell barrier integrity and attenuated pulmonary vascular leak [157].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) is firstly discovered in non‐small cell lung cancer, which can promote the proliferation, metastasis, and invasion of tumor cells, and participate in epigenetic processes and cell cycle . Recent studies have found that MALAT1 is involved in the development of immune inflammatory diseases . Puthanveetil et al found that MALAT1 can increase high glucose‐induced inflammatory cytokines tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6) expression.…”
Section: Introductionmentioning
confidence: 99%